EXAMINING CHALLENGES NOVICE FEMALE PRINCIPALS ENCOUTER REGARDING TEACHER ATTRITION: RURAL PRIMARY SCHOOLS - Saltiel Khololo Collen Mataboge; Mapula Rebecca Mabusela (CV. RADJA PUBLIKA, 2025)
This conceptualized paper sought to examine the challenges novice female principals encounter regarding teacher attrition in rural primary schools. Teacher attrition, particularly in rural areas poses a significant threat to the stability and performance of schools. The main question guiding this study is: What are the key challenges that novice female principals face in managing teacher attrition in rural primary schools? A qualitative approach is adopted, encompassing an intensive review of scholarly books and articles from (2018-2024) on the topic under discussion. An interpretive paradigm is utilized to understand the academic perspectives focusing on principals in their unique rural contexts. Findings revealed that novice female principals face multiple challenges which include limited resources, professional isolation, lack of mentorship and cultural dynamics that exacerbate teacher turnover. In addition, inadequate support from local education authorities further complicates their ability to retain staff. The significance of the study lies in its potential to inform policy and leadership training programs designed to the needs of female principals within the rural settings. Limitations include the exclusive reliance on literature-based data which may require future empirical studies to validate the findings. The study highlights the need for targeted strategies to support novice female principals in mitigating teacher attrition and enhancing school stability